Genetic identification of lamniform and carcharhiniform sharks using multiplex-PCR - Mendonca, F. F. [UNESP]; Hashimoto, D. T. [UNESP]; De-Franco, B. [UNESP]; Porto-Foresti, Fábio [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Oliveira, C. [UNESP]; Foresti, Fausto [UNESP] (Springer, 2010)
Nowadays, because of the constant increase in the capture and trade of sharks all over the world and reports of several species already showing important signs of over-exploitation, the establishment of registration mechanisms, evaluation and fishery control become urgent. Morphological identification of captured sharks is very difficult, and sometimes impossible, due to the removal of the animals' parts. At this point, techniques of genetic identification through the molecular markers are considered essential tools for fishery monitoring. In this study, we present a method of multiplex-PCR, based on the gene Cytochrome Oxidase I, with species-specific primers developed for simultaneous identification of nine species of lamniform and carcharhiniform sharks, some of which are worldwide distributed.
Keywords: Sharks identification; Trade monitoring; Molecular markers; Cytochrome oxidase I; Multiplex-PCR